Making waves: Lessons learned from the COVID-19 anthropause in the Netherlands on urban aquatic ecosystem services provisioning and management. (1st September 2022) - Armstrong, Margaret; Aksu Bahçeci, Hazal; van Donk, Ellen; Dubey, Asmita; Frenken, Thijs; Gebreyohanes Belay, Berte M.; Gsell, Alena S.; Heuts, Tom S.; Kramer, Lilith; Lürling, Miquel; Ouboter, Maarten; Seelen, Laura M.S.; et al.
Highlights: Anthropause-derived decreases in boating led to improved urban canal water quality. Anthropause-increased fishing, bathing and nature visits could cause degradation. Lessons from COVID-19 human-ecosystem interactions can inform management practices. Abstract: The anomalous past two years of the COVID-19 pandemic have been a test of human response to global crisis management as typical human activities were significantly altered. The COVID-instigated anthropause has illustrated the influence that humans and the biosphere have on each other, especially given the variety of national mobility interventions that have been implemented globally. These local COVID-19-era restrictions influenced human-ecosystem interactions through changes in accessibility of water systems and changes in ecosystem service demand. Four urban aquatic case studies in the Netherlands demonstrated shifts in human demand during the anthropause. For instance, reduced boat traffic in Amsterdam canals led to improved water clarity. In comparison, ongoing service exploitation from increased recreational fishing, use of bathing waters and national parks visitation are heightening concerns about potential ecosystem degradation. We distilled management lessons from both the case studies as well as from recent literature pertaining to ecological intactness and social relevance. Equally important to the lessons themselves, however, is the pace at which informed management practices are established after the pandemic ends, particularly as many communities currently recognize the importance of aquatic ecosystems and are amenable to their protection. Graphical abstract: Image, graphical abstract